Coracoid Process Avulsion Fracture at the Coracoclavicular Ligament Attachment Site in an Osteoporotic Patient with Acromioclavicular Joint Dislocation. (17th July 2016) - Onada, Yoshihiro; Umemoto, Takahisa; Fukuda, Kimitaka; Kajino, Tomomichi
Abstract : Coracoid fractures are uncommon, mostly occur at the base or neck of the coracoid process (CP), and typically present with ipsilateral acromioclavicular joint (ACJ) dislocation. However, CP avulsion fractures at the coracoclavicular ligament (CCL) attachment with ACJ dislocation have not been previously reported. A 59-year-old woman receiving glucocorticoid treatment fell from bed and complained of pain in her shoulder. Radiographs revealed an ACJ dislocation with a distal clavicle fracture. Three-dimensional computed tomography (3D-CT) reconstruction showed a small bone fragment at the medial apex of the CP. She was treated conservatively and achieved a satisfactory outcome. CP avulsion fractures at the CCL attachment can occur in osteoporotic patients with ACJ dislocations. Three-dimensional computed tomography is useful for identifying this fracture type. CP avulsion fractures should be suspected in patients with ACJ dislocations and risk factors for osteoporosis or osteopenia.